CoQ10 and Vitamin A Supplementation Support Voice Rehabilitation. A Double-Blind, Randomized, Controlled, Three-Period Cross-Over Pilot Study - Ruoppolo, Giovanni; Longo, Lucia; Pescerelli, Patrizia; Mango, Chiara; Nicastri, Maria; Flaccadoro, Flavia; Mancini, Patrizia; Greco, Antonio; De Vincentiis, Marco (Frontiers in Pharmacology, 2019)
Objectives: To evaluate the effectiveness of an adjuvant therapy (CoQ10 in its water-soluble form and vitamin A) in supporting voice rehabilitation in a large group of patients with muscle tension dysphonia (MTD). Study Design: Twelve-week, double-blind, randomized, controlled, three-period cross-over pilot study. The primary endpoint was the change in the Dysphonia Severity Index (DSI) over the 12-week study period. Secondary endpoints were the changes in the subcomponents of DSI, including MPT, F0-high, I-low, and jitter. Exploratory endpoints were the changes in the Shimmer and in Voice Handicap Index (VHI). Methods: Patients were randomly assigned in a 1:1 ratio to two counter-balanced arms. Group A (ADJ-PLA) patients were administered QTer 300 mg and Vit A acetate 500.000 Ul/g 1 mg twice daily for a 4-week intervention period, followed by a 4-week period of wash-out, and then were submitted to a last 4-week period of placebo. Patients in Group B (PLB-ADJ) were given the treatment period in reverse order. Both groups received a 45-min voice therapy in a group format once a day for 4 weeks during the first and the second active periods. The therapy was held during the wash-out period. Results: The analysis of main time effect indicated a trend toward recovery of vocal function regardless of group assignment. A significant time by group effect was found on DSI [F = 3.4 (2.5, 80.5), p = 0.03], F0-high [F = 4.5 (2.6, 82.9), p = 0.008] and Shimmer [F = 3.6 (1.5, 46.9), p = 0.048], under CoQ10 and Vit A treatment, with a small effect size. There was no significant time by group effect on the other study measures, namely MPT, I-low, VHI. Conclusions: A trend toward recovery of vocal function was observed in all the patients, likely due to voice rehabilitation. The improvement of DSI was greater under CoQ10 and Vitamin treatment, indicating a more pronounced improvement of vocal quality under adjuvant therapy. The study protocol was reviewed and approved by the Ethics Committee of Policlinico Umberto I Hospital, Rome, Italy Rif. 3069/13.02.2014.